Ambiguity of ecological conditioning of great cultural | transformations. Two examples: European Plains at the end of the ice age and early holocene Sahara - Schild, Romuald; Wendorf, Fred (Anthropological Review, 1978)
In the article, an ecological-demographic interpretation of great cultural shifts is attempted. The first of the two examples employed for this purpose is concerned with climatic changes and accompanying transformations in the cultural systems of human groups living on the European Plains around 9900-8300 B.C. In particular, the disappearance of characteristics for the Alleröde tool assemblages with arc-shaped blades (related to the warmer phase of human groups pursuing the trapper type of hunting) and the appearance of the new technological complex with projectile points (groups related to the cooler phase and exploiting reindeer). Origin of neolithic in Northern Africa is used as the second example. The enlargement of areas accessible for human exploitation due to climatic changes resulting in the spread of vegetation over the previously deserted belt of Sahara during the period immediately preceding the appearance of agriculture (epipaleolithic) gave rise to demographic development and, indirectly, to changes in the whole economic pattern.